Analysis of Web-Based Library Information System Design for State Senior High School 13 Samarinda - Widiarti, Sylvania Ayu; Fahmi, Muhammad; Pahrudin, Pajar (Sebatik, 2025)
The school library has an important role in supporting the teaching and learning process in schools, one of which is the library at SMA Negeri 13 Samarinda. The library has a collection of books totaling hundreds of titles. The book collection is grouped into several categories such as general subject books, religious books, newspapers, comics, fairy tales, and story books, and many other books. With many different types of book groups, the library at SMA Negeri 13 Samarinda still uses a conventional system where the library admin uses archives or notebooks placed in cupboards such as book borrowing and book return archives, this often makes books that will be borrowed by students difficult to find. The goal is to be able to improve library services at SMA Negeri 13 Samarinda. The conclusion is that the Library Application at SMA Negeri 13 Samarinda was successfully created using Visual Basic 6.0. With this system, it will facilitate the presentation of reports related to the processing of library book data at SMA Negeri 13 Samarinda.